PENGARUH KNOWLEDGE SHARING DAN INFORMATION TECHNOLOGY RELATEDNESS TERHADAP KINERJA PEGAWAI PADA PANGKALAN SARANA OPERASI BEA DAN CUKAI TIPE B SORONG - Nengsy Wasolo; Wisang Candra Bintari; Ramli Lewenussa; Muhammad Ali; RAIS DERA PUA RAWI (Journal of Management and Accounting (JMA), 2025)
Abstract. This study aims to determine (1) the effect of knowledge sharing on employee performance at the Pangkalan Sarana Operasi Bea Dan Cukai Tipe B Sorong. (2) the influence of information technology relatedness on employee performance at the Pangkalan Sarana Operasi Bea Dan Cukai Tipe B Sorong. (3) the influence of knowledge sharing and information technology relatedness on employee performance at the Pangkalan Sarana Operasi Bea Dan Cukai Tipe B Sorong. This study uses descriptive and correlation methods using a quantitative approach. The population in this study were employees at the Pangkalan Sarana Operasi Bea Dan Cukai Tipe B Sorong. The sampling technique used Saturated Sampling with a sample size of 40 people. The data collection technique uses a questionnaire that has been tested for validity and reliability. The data analysis technique used multiple regression. The results showed that: Knowledge Sharing has a positive effect on employee performance at the Pangkalan Sarana Operasi Bea Dan Cukai Tipe B Sorong. This is evidenced by the tcount of 5.327> 2.02619 with a significant value of 0.000 < from the significance level of 0.05 and the regression coefficient having a positive value of 0.381. Information Technology Relatedness has a positive effect on employee performance at the Pangkalan Sarana Operasi Bea Dan Cukai Tipe B Sorong. This is evidenced by the tcount of 5.327 > 2.02619 with a significant value of 0.000 < from the significance level of 0.05. and the regression coefficient has a positive value of 0.192. Knowledge sharing and information technology relatedness have a positive effect simultaneously on employee performance at the Pangkalan Sarana Operasi Bea Dan Cukai Tipe B Sorong. This is evidenced by the value of Fcount of 12.949 > Ftable of 3.25 with a significance of 0.000 < from the significance level of 0.05 and the regression coefficient having a positive value of 0.412.